Perancangan Interior Student Social Space di Universitas Kristen Petra Surabaya (Konsekuensi Alih Fungsi Material Shipping Container) - Chandra, Irvan Andreanto; Kusumarini, Yusita; Suryanata, Linggajaya (Intra, 2015)
Apart from a routine and systematic lectures in an university, it turns out that various students activities are a supportive activities of the main activities, which is the lectures itself. This activity is a spontaneous activity in a short period of time but done as routines in an everyday life, both by an individual or groups (social) such as; relaxing sit/resting while waiting for the lectures time, chatting with friends, eating and drinking, and so on. This design aim to create an area (space) that can facilitate those activities specifically and optimally. The designer desires to utilize the space of shipping container material is based on the reality that the accumulation of shipping containers in the harbor is increasing due to the cheaper budget in the making of a new one than reusing the old ones.                This design applies the design thinking methods that started from a data collection, programming, then initiation method and design visualization that ended with the realization phase and design evaluation. The finding results in 3 student social space designs from a functional shift of shipping container material in Petra Christian University Surabaya.